Upaya Meningkatkan Hasil Belajar Siswa Melalui Model Pembelajaran Round Club - Idawati Idawati (JURNAL GLOBAL EDUKASI, 2022)
Abstract: In developing a learning method a teacher must be able to adapt the method he chooses to the conditions of the students, subject matter, and existing facilities. One of the abilities that must be chosen by a teacher in improving his professional competence is the ability to develop learning methods. In carrying out education, an educator must pay attention to these developmental aspects. Of the many components of education, the teacher is a very important factor in efforts to improve education. To have the ability to manage learning (pedagogic competence) well, of course teachers need to understand the important elements related to learning management. This Classroom Action Research is located at UPTD SDN 013853 Selawan kec. Kota Kisaran Timur. The subjects in this study were Class VI students of UPTD SDN 013853 Selawan. Based on the results of the discussion, it can be concluded that the results of the learning process prior to research on the subject matter of Earth and the Universe in Science Lessons through the Round Club learning model achieved an average value of 55%. After being motivated to do research through cycle I and cycle II reflection and recommendations the average value reached 85.8%. Keywords: learning management; round club  Abstak: Dalam mengembangkan metode pembelajaran seorang guru harus dapat menyesuaikan antara metode yang dipilihnya dengan kondisi siswa, materi pelajaran, dan sarana yang ada. Salah satu kemampuan yang harus dipilih oleh seorang guru dalam meningkatkan kompetensi profesinya ialah kemampuan mengembangkan metode pembelajaran. Dalam melaksanakan pendidikan, seorang pendidik harus memperhatikan aspek-aspek perkembangan tersebut. Dari sekian banyak komponen pendidikan, guru merupakan faktor yang sangat penting dalam usaha peningkatan pendidikan. Untuk memiliki kemampuan mengelola pembelajaran (kompetensi pedagogik) dengan baik, tentu saja guru perlu memahami unsur-unsur penting yang berkaitan dengan manajemen pembelajaran. Penelitian Tindakan Kelas ini berlokasi di UPTD SDN 013853 Selawan kec. Kota Kisaran Timur. Subjek dalam penelitian ini adalah Siswa Kelas VI UPTD SDN 013853 Selawan. Berdasarkan hasil pembahasan dapat disimpulkan hasil proses belajar sebelum penelitian pada materi pokok Bumi dan Alam Semesta Pada Pelajaran IPA melalui model pembelajaran Round Club mencapai nilai rata-rata 55%. Setelah termotivasi dilakukan penelitian melalui siklus I dan siklus II refleksi dan rekomendasi nilai rata-rata mencapai 85,8%. Kata kunci: manajemen pembelajaran; round club